The Roles and Teaching Strategies of Teachers in The Era of Disruptions: Study on Policy of Education Minister Nadiem Anwar Makarim in Hadith Perspective - Kadi Kadi; Dewi Wati; Indah Sari (Didaktika Religia, 2020)
Educators are the best curriculum for applying knowledge, culture, and science. As for realizing all these goals, it is necessary to have the right idea. From that, the ideas conveyed by Nadiem Makarim the Indonesian Minister of Education, will be correlated in the hadith perspective. This idea can be drawn from five important points, namely, class discussion, the role of students in teaching and learning activities, fostering the social spirit of students, discovering studentâ€™s identities, cooperation between teachers and students. Where these ideas have been conveyed indirectly through the hadiths, which are, part of the Prophet is learning. Hadiths found through literature study are the Kitab Syarah Bukhari, Fathul Baari, Sahih Muslim, and journals. The method used in this Takhrij al-Hadith is a qualitative study with the sanad criticism approach to determine the authenticity of a hadisth. In the sanad criticism method, the writer uses the Lidwa Pustaka i-software assistance method. Hadith found with the bil maâ€™na redaction method. So that there are 4 hadiths in the study. The first hadith in Shohih Bukhari no. 5514 regarding the method of question and answer the Prophet. Second, in Shohih Bukhori no. 77 about the virtue of konwledge and teaching. Third, in Shohih Muslim no. 4831 about growing the social soul. Fourth, in Sahih Bukhari no. 5567 about please help. The results of this study indicate tht the hadiths are muttashil (continued) so that the Prophet and his narrators have the predicate â€˜fair and dlobitous so that these.